Situación sociofamiliar de los adultos mayores del cantón El Guabo y su incidencia en la calidad de vida, 2022 - Molina Vásquez, John Adrian (Machala: Universidad Técnica de Machala, 2023)
The main objective of the project is to determine the influence of the socio-family situation on the quality of life of the elderly in the canton of El Guabo, year 2022. The topic is important because it introduces the problems of a vulnerable sector of the population that, due to their helplessness, cannot support themselves. The specific objectives are aimed at determining the economic income of the families of El Guabo who live with older adults, identifying the family environment and its influence on the communication processes of older adults in the canton, identifying the ways in which families solve the daily needs of the elderly, and determining the strategies promoted by local authorities to improve the quality of life of older adults. On the other hand, it should be mentioned that the sociological foundation of the work is structuralist functional, where it is important to note that from this theory the aging stage alters the development of family groups, which are the core of society, altering family relationships and their functioning, so it is important that the State pays attention to the complexities of older adults. Currently in Ecuador, the number of older adults comprises 7.4% of the 17.5 million Ecuadorians, 786,000 live in vulnerable situations, which means that 6 out of 10 of this group are economically dependent on their families. Within the Canton of El Guabo there are 123 beneficiaries of the programs and projects implemented by the Municipal Decentralized Autonomous Government through the Patronato de Amparo Social. The research approach is quantitative, the method is hypothetical deductive and to collect information surveys are applied to older adults and their families, the results allow a diagnosis of the situation. A proposal was developed to sensitize the families of the canton of El Guabo, through workshops to improve the lives of older adults, since there are 123 who attend the Patronato de Amparo Social and who would benefit from the workshops to perform recreational activities, also carrying out a follow-up through home visits to know their physical condition and social integration. As a result of the investigation, it was identified that 57% of the families have an income of less than $400, which is a low income, since these families live with an older adult, taking into consideration that he/she is not an economically active person. Another fact that was revealed is that 65% of the older adults receive economic assistance that covers part of their expenses, but the great majority suffer from some illness, which means that they must constantly buy medicine, and 35% of the adults stated that they do not receive any type of assistance. The government entity that helps the elderly in El Guabo is the Ministry of Economic and Social Inclusion with 56%, while only 10% receive help from the municipality. Of the total number of older adults, only 57% receive the human development voucher.
El proyecto tiene como objetivo principal, determinar la influencia de la situación socio familiar en la calidad de vida del adulto mayor del cantón El Guabo, año 2022. El tema reviste de importancia pues introduce en la problemática de un sector vulnerable de la población que por su indefensión no pueden auto sustentarse. Los objetivos específicos se encaminan en determinar el ingreso económico de las familias de El Guabo que viven con adultos mayores, identificar el ambiente familiar y su influencia en los procesos de comunicación de los adultos mayores en el cantón, identificar las formas como las familias resuelven las necesidades cotidianas de los ancianos y determinar las estrategias que promueven las autoridades locales para el mejoramiento de la calidad de vida del adulto mayor. Por otra parte, se debe mencionar que el fundamento sociológico del trabajo es funcional estructuralista, donde es importante señalar que desde esa teoría la etapa del envejecimiento altera el desenvolvimiento de los grupos familiares, que son el núcleo de la sociedad, alterando relaciones familiares y su funcionamiento, por ello es importante que el Estado preste atención a las complejidades de los adultos mayores. Actualmente en el Ecuador la cantidad de adultos mayores comprende un 7,4% total de los 17,5 millones de ecuatorianos, 786.000 viven en situación vulnerable lo cual expresa que 6 de cada 10 de este grupo dependen económicamente de sus familias. Dentro del Cantón El Guabo existen 123 beneficiarios de los programas y proyectos que implementa el Gobierno Autónomo Descentralizado Municipal a través del Patronato de Amparo Social. En cuanto al enfoque de investigación es cuantitativo, el método es hipotético deductivo y para recoger información se aplica encuestas a los adultos mayores y sus familias, los resultados permiten un diagnóstico sobre la situación. Se elaboró una propuesta para la sensibilización a las familias del cantón El Guabo, mediante talleres para mejorar la vida de los adultos mayores, ya que son 123 los que asisten al Patronato de Amparo Social y que se beneficiarían de los talles para que realicen actividades de recreación, llevando también un seguimiento mediante visitas domiciliarias para conocer su estado físico e integración social. Como resultado de la investigación se identificó que el 57% de las familias tienen ingresos menores a $400 siendo un ingreso económico bajo, ya que estas familias viven con un adulto mayor, tomando en consideración que no es una persona económicamente activa, otro dato que manifestaron es que el 65% de los adultos mayores reciben una ayuda económica que cubre parte de sus gastos, pero la gran mayoría padece de alguna enfermedad, que representa la compra constante de medicamentos y el 35% de los adultos declararon que no reciben ningún tipo de ayuda. La entidad gubernamental que ayuda a los adultos mayores en el cantón El Guabo es el Ministerio de Inclusión Económica y Social con el 56%, mientras que solo el 10% recibe ayuda por parte del municipio. Del total de adultos mayores solo el 57% de ellos reciben el bono de desarrollo humano.
Keywords: ADULTO MAYOR; SITUACION FAMILIAR; ATENCION INTEGRAL; CALIDAD DE VIDA